(untitled) (Journal of actual problems of jurisprudence, 2019)
The article considered some problems related to identification of status and protection of rights of the suspected person in the criminal process of the Republic of Azerbaijan, as well as highlighted some provisions of vital importance provided in the Constitution of the Republic of Azerbaijan and criminal procedure legislation entered into force on 1 September 2000 about protection of rights and legal interests of a person and suspect. The article made some proposals with regard to improvement of procedural legislation and underlined problems of special importance which need its solution and regulation in the legislative level.